2003
DOI: 10.1007/s00705-002-0908-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of rabbit haemorrhagic disease virus in France between 1993 and 2000, and the characterisation of RHDV antigenic variants

Abstract: The first molecular epidemiological study of Rabbit haemorrhagic disease virus undertaken in France between 1988 and 1995, identified three genogroups, two of which (G1, G2) disappeared quickly. We used immunocapture-RT-PCR and sequencing to analyse 104 new RHDV isolates collected between 1993 and 2000. One isolate was obtained in 2000 from a French overseas territory, the Reunion Island. The nucleotide sequences of these isolates were aligned with those of some French RHDV isolates representative of the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
128
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(140 citation statements)
references
References 21 publications
9
128
0
3
Order By: Relevance
“…The study showed the lack of amplification of STR 2012 genetic material with P1 primer (5182-5201) from the C-terminus of the RHDV RdRp polymerase gene. The primer set P1/P2, originally proposed by Guittré et al (21), has been used for many years in many laboratories for routine amplification of classic RHDV strains, including HA-negative phenotypic variants (23,26). Similar difficulties were encountered in the amplification of cDNAs of the samples L1-L6 with the pair of primers N3-N4 encoding the N-terminal part of the VP60 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed the lack of amplification of STR 2012 genetic material with P1 primer (5182-5201) from the C-terminus of the RHDV RdRp polymerase gene. The primer set P1/P2, originally proposed by Guittré et al (21), has been used for many years in many laboratories for routine amplification of classic RHDV strains, including HA-negative phenotypic variants (23,26). Similar difficulties were encountered in the amplification of cDNAs of the samples L1-L6 with the pair of primers N3-N4 encoding the N-terminal part of the VP60 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the presence of the classic form of RHDV strains with an altered haemagglutination (HA) profile (phenotypic HAnegative variant), RHDV strains known as antigenic and genetic variants (RHDVa), a moderately pathogenic calicivirus (MRCV), a recently new French RHDV variant, and non-pathogenic caliciviruses (RCV, RCV-A1, Lambay, 06-11) (1,4,5,6,24,26,27,34,36). Pathogenic RHDV and RHDVa isolates belong to one serotype (2,3,10,36).…”
Section: Introductionmentioning
confidence: 99%
“…Stopniowy zanik występowania poszczególnych grup genetycznych na świecie obserwuje się od końca lat 90. (44,54). Enklawą klasycznego RHDV w Europie był do niedawna Półwysep Pirenejski, gdzie diagnozowano go jeszcze 2008 r. (3,4,22).…”
Section: Chorobotwórcze Typy (Warianty) Wirusa Rhdunclassified
“…Na zakażenie podatne są jedynie króliki Oryctolagus cuniculus w takim samym przedziale wiekowym, jak w przypadku RHDV, głównie hodowlane, ale także dzikie (14, 62). Wszystkie izolaty podtypu RHDVa wyosobnione dotąd na świecie należą do genogrupy G6 (11,36,44,48,54). W porównaniu do klasycznego wirusa RHD, podtyp RHDVa wykazuje znaczne zmiany genetyczne, sprzyjające selekcji i zwiększające moż-liwości przetrwania.…”
unclassified
“…For this purpose, RNA was extracted and purified from 100 µL of liver exudate obtained after thawing by an immunocapture assay [17] or with the RNeasy Kit (Qiagen, Venlo, The Netherlands). Then, a 559 bp fragment from the 3' end of the gene was amplified by RT-PCR with RHDVAU and RHDVAL degenerated primers and for two isolates, the complete VP60 encoding sequence was amplified [18]. The amplified products were analysed by conventional electrophoresis on agarose gel and purified (Geneclean II kit, Bio 101, Qbiogene, Montreal, Canada).…”
Section: Viral Sequence Analysismentioning
confidence: 99%